2018
DOI: 10.1177/0193945918815462
|View full text |Cite|
|
Sign up to set email alerts
|

Nurses’ Safety Motivation: Examining Predictors of Nurses’ Willingness to Report Medication Errors

Abstract: Medication errors are common in health care settings. Safety motivation, such as willingness to report error, is needed to contain medication errors. Limited evidence exists about measures to enforce nurses’ safety motivation. The purpose of this study was to test a proposed model explaining the mechanism by which organizational and social factors influence nurses’ safety motivation. Survey for this cross-sectional study was mailed to a random sample of 500 acute care nurses. Data collection started in January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 39 publications
(88 reference statements)
2
14
0
Order By: Relevance
“…This finding was supported within the literature and found that the leadership response not only influenced nurses' desire to report future errors but also reporting errors by others. 6,9,24 We found that positive leadership response and support of error reporting built a safety culture on the unit; however, only a few participants expressed this experience. Inconsistencies in nurse leaders' actions around error reporting were not identified in the literature.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This finding was supported within the literature and found that the leadership response not only influenced nurses' desire to report future errors but also reporting errors by others. 6,9,24 We found that positive leadership response and support of error reporting built a safety culture on the unit; however, only a few participants expressed this experience. Inconsistencies in nurse leaders' actions around error reporting were not identified in the literature.…”
Section: Discussionmentioning
confidence: 83%
“…An interview guide with open-ended and probing questions was developed to ensure consistency of dialogue among the groups. The questions were developed from a literature review [5][6][7][8][9] and evaluated by the research team for relevance and ability to answer the research aim (see Supplemental Digital Content, Table 1, available at: http://links. lww.com/JNCQ/B226).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that medication errors and near misses were underreported, which is consistent with prior studies and our previous work. 45 The underreporting of medication errors and near misses limits our ability to confirm the relationship between medication errors and fatigue. Fatigue was measured using a self-report measure.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…2 Accurate and complete ME reporting is essential to quality improvement efforts, as are holding healthcare providers accountable and implementing effective initiatives to promote safety in health care. 3 However, the literature estimates that 25-70% of all MEs are reported. 4 According to the Institute for Safe Medication Practices, these ME reporting rates underrepresent the real figure and are "just the tip of iceberg".…”
Section: Introductionmentioning
confidence: 99%